Low Baseline High-Sensitive C-Reactive Protein is Associated with Coronary Atherosclerosis Regression: Insights from the MILLION Study - Sakata, Kenji (J Atheroscler Thromb, 2019)
Aim: The prospective, randomized, multicenter Myocardial Ischemia Treated with Percutaneous Coronary Intervention and Plaque Regression by Lipid Lowering & Blood Pressure Controlling assessed by Intravascular Ultrasonography (MILLION) study demonstrated that combined treatment with atorvastatin and amlodipine enhanced coronary artery plaque regression. Although the baseline high-sensitive C-reactive protein (hs-CRP) reportedly plays an important role in atherogenesis, few data exist regarding the relationship between hs-CRP and plaque regression in patients receiving a combined atorvastatin and amlodipine therapy. Methods: A total of 68 patients (male, 55; mean age, 64.2 years) with baseline and follow-up 3-dimensional intravascular ultrasound examinations in the MILLION study were stratified by baseline hs-CRP level quartiles. The serial measurements of lipid, blood pressure, and percentage changes in the plaque volume were compared between the groups, and the factors associated with the percentage change in the plaque volume were assessed. Results: There were no significant between-group differences in the extent of change in low-density lipoprotein cholesterol (LDL-C) or systolic and diastolic blood pressure after 18–24 months of treatment. The percentage change in the plaque volume showed a linear association with the baseline hs-CRP (p for trend < 0.05); however, there was no correlation with changes in LDL-C or systolic and diastolic blood pressure. In the multiple regression analysis, the baseline hs-CRP level was independently associated with the percentage change in the plaque volume (β = 0.29, p = 0.022). Conclusions: Coronary plaque regression was associated with the baseline hs-CRP level in patients treated with a combined lipid- and blood pressure-lowering therapy.